ANALISIS MATERIAL REQUIREMENT PLANNING PRODUK BODY SCRUB POWDER PADA CV. DENARA DUTA MANDIRI - monica, shinta; Setiawan, Putu Yudi (E-Jurnal Manajemen; Vol 8 No 5 (2019)DO - 10.24843/EJMUNUD.2019.v08.i05.p13, 2019)
Improper Inventory management can results in deficiency or excess inventory of raw materials. One concept that can be used to plan and control raw materials is the Material Requirement Planning (MRP) system. The purpose of this study is to find out the number of net requirements, size of order, time of order, and methods that produce the lowest cost for each raw materialData analysis techniques are carried out, namely making production master schedules, determining net requirements, determining lot size (lot for lot method and part period balancing), determining optimal lot sizing and determining the time of ordering raw materials or making MRP tables. The results showed that trend projection forecasting had the smallest forecasting error with 82 kg forecasting results. Determination of order size or lot sizing obtained by the best lot sizing method is part period balancing which results in a total inventory cost of Rp. 338.911.24 where the total cost is lower, compared to the total inventory cost lot for lot method which is Rp. 795.000. Keywords :  Material Requirement Planning (MRP), Forecasting, Sizing Lot, Lot For Lot, Part Period Balancing